AKIBAT HUKUM JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN MENURUT UU NOMOR 42 TAHUN 1999 - Muhammad Hilmi Akhsin; Anis Mashdurohatun (Jurnal Akta, 2017)
ABSTRACTFiduciary agreements by notarial deed are not sufficient, but should be continued with fiduciary registrants. Fiduciary agreements set forth in notarial deeds without registration do not grant preferential rights to fiduciary recipients. Whereas the objective of Law Number 42 Year 1999 is basically to provide legal protection for creditors from losses caused by default from debtor. From this, the authors in this thesis take the title "Consequences of Fiduciary Guaranty Laws Not Registered According to Law Number 42 Year 1999." With the scope of the issues covered include: (1) How the procedure or implementation of credit with fiduciary guarantee in Indonesia; (2) What are the constraints and solutions in the implementation of credit with fiduciary guarantee in Indonesia, and (3) What are the consequences of fiduciary guarantee law enlisted under Law No. 42 of 1999.To obtain the results of research from these problems, the authors use the scientific method with an approach that is juridical empirical and normatiif. Empirically that is researching secondary data first and then continued by conducting research of primary data in field. The jurisdiction is to study the rules that exist with the problem in the perusal.Furthermore, from the results of the research can obtain the understanding that the first, that the credit agreement made by debtors and creditors is the principal agreement that refers to the general principles of the agreement, while the imposition of fiduciary collateral meruapakan follow-up agreement or accesoir, which registers it has been regulated by Law No. 42 of 1999 , And set further through Government Regulation No. 21 of 2015; Second, the registration of fiduciary security is a creditor's obligation, but sometimes the creditor does not register it, for cost reasons or because the treaty deed is made under the hand. Therefore, the right of the fiduciary guarantee certificate is categorized as a treaty under the hand. Therefore, the solution taken by the creditors can make the settlement by deliberation or applying through the judiciary. Third, Fiduciary Guarantees must be made by the Deed of Natariil (Notarial Deed) and registered to the Office of the Ministry of Justice and Human Rights, in order to have executorial power, in addition, the creditor will obtain the preferred right. If fiduciary warranties are not made under the hands and are not registered in accordance with legislative provisions, they have no executorial force, and the right of preference and may become void (vernitigbarheid).Whereas to further realize the main principle of Fiduciary Guarantee provides legal protection for the parties, it is necessary to revise the regulation of fiduciary guarantee in legislation in order to give more legal certainty.Keywords: Fiduciary Security, Registration Procedures, and Legal EffectsABSTRACT Fiduciary agreements by notarial deed are not sufficient, but should be continued with fiduciary registrants. Fiduciary agreements set forth in notarial deeds without registration do not grant preferential rights to fiduciary recipients. Whereas the objective of Law Number 42 Year 1999 is basically to provide legal protection for creditors from losses caused by default from debtor. From this, the authors in this thesis take the title "Consequences of Fiduciary Guaranty Laws Not Registered According to Law Number 42 Year 1999." With the scope of the issues covered include: (1) How the procedure or implementation of credit with fiduciary guarantee in Indonesia; (2) What are the constraints and solutions in the implementation of credit with fiduciary guarantee in Indonesia, and (3) What are the consequences of fiduciary guarantee law enlisted under Law No. 42 of 1999.To obtain the results of research from these problems, the authors use the scientific method with an approach that is juridical empirical and normatiif. Empirically that is researching secondary data first and then continued by conducting research of primary data in field. The jurisdiction is to study the rules that exist with the problem in the perusal.Furthermore, from the results of the research can obtain the understanding that the first, that the credit agreement made by debtors and creditors is the principal agreement that refers to the general principles of the agreement, while the imposition of fiduciary collateral meruapakan follow-up agreement or accesoir, which registers it has been regulated by Law No. 42 of 1999 , And set further through Government Regulation No. 21 of 2015; Second, the registration of fiduciary security is a creditor's obligation, but sometimes the creditor does not register it, for cost reasons or because the treaty deed is made under the hand. Therefore, the right of the fiduciary guarantee certificate is categorized as a treaty under the hand. Therefore, the solution taken by the creditors can make the settlement by deliberation or applying through the judiciary. Third, Fiduciary Guarantees must be made by the Deed of Natariil (Notarial Deed) and registered to the Office of the Ministry of Justice and Human Rights, in order to have executorial power, in addition, the creditor will obtain the preferred right. If fiduciary warranties are not made under the hands and are not registered in accordance with legislative provisions, they have no executorial force, and the right of preference and may become void (vernitigbarheid).Whereas to further realize the main principle of Fiduciary Guarantee provides legal protection for the parties, it is necessary to revise the regulation of fiduciary guarantee in legislation in order to give more legal certainty.Keywords: Fiduciary Security, Registration Procedures, and Legal Effects